India's low temperature thermal desalination technology: Water diplomacy with Small Island Developing States in the Indo-Pacific Region. (2nd July 2020) - Guduru, Sameer; Bajaj, Pushp; Gonsalves, Oliver Nelson
ABSTRACT: Water scarcity is a long-standing issue among Small Island Developing States (SIDS). The issue is further magnified by climate change and is emerging as an existential threat to SIDS. Ironically, these states are among the lowest contributors to greenhouse gas emissions which is the primary cause for climate change. Due to limited indigenous economic and technological capacity and capability, SIDS often require external assistance. In this context, this article explores the opportunity for India to offer its Low Temperature Thermal Desalination (LTTD) technology to tackle water scarcity in SIDS. The article will assess the advantages of LTTD over conventional options such as membrane-based and other distillation-based techniques. By promoting the technology through bilateral and multilateral mechanisms, India can reinforce its position as a major stakeholder in the Indo-Pacific and as a responsible actor committed to combating and mitigating effects of climate change.